Factors influencing type 2 diabetes self-management practices in rural Bangladesh: a qualitative investigation - Chowdhury, Hasina Akhter; Billah, Baki; Dipa, Shamia Akther; Kabir, Ashraful; Rahman, A. K. M. Fazlur; Ali, Liaquat; Joham, Anju E.; Harrison, Cheryce L. (Frontiers in Public Health, 2025)
IntroductionType 2 diabetes mellitus (T2DM) is a prevalent, chronic health condition of global significance, with low- and middle-income countries (LMICs) disproportionately affected. Diabetes self-management practices (DSMP) are the gold-standard treatment approach, yet uptake remains challenge in LMICs.Purpose of the studyThis study aimed to explore the barriers to and facilitators of DSMP and preferences for intervention design and delivery in Bangladesh, an LMIC, with prevalent T2DM.MethodsSixteen qualitative focus group discussions (FGDs) with adults with T2DM and their caregivers were conducted in rural Bangladesh to explore preferences, barriers, and facilitators for community DSMP-related intervention programs. Data were thematically analyzed using a deductive theoretical domains framework (TDF) underpinned by the socio-ecological model.ResultsOverall, 117 participants (n = 58 with T2DM and n = 59 caregivers) were included in the analysis. Five overarching themes were identified, including (i) implementation of DSMP, (ii) community spirit and interconnectedness, (iii) environmental influences, (iv) healthcare professionals’ role in DSMP, and (v) government support. Key barriers to DSMP identified for T2DM patients include knowledge implementation gaps, cultural practices, limited resources, and financial constraints. Facilitators include motivation, support from family and peers, and religious practices. Rural Bangladeshis prefer programs delivered at community clinics, viewing them as reliable, culturally appropriate central ‘hubs’ to assemble.ConclusionBarriers to and facilitators of DSMP were identified, and preferences for intervention design and delivery for implementing DSMP were explored. The findings provide a foundation for the critical need to implement programs that improve DSMP in Bangladesh, with the potential to translate to other LMIC settings.